In Vitro Screening for Antimicrobial and Antioxidant of a meditational plant: Ziziphus jujube leaves - Islam, Shariful (2021)
The current study explore was designed for the investigation of antimicrobial and antioxidant activity of crude methanol extract of the plant Ziziphus jujuba. The crude methanol extract and other extracts showed considerable total antioxidant activity and reducing capacity. In DPPH scavenging test, the crude extract showed 83.02% scavenging having IC50 of 22.23 μg/ml. Amongst the fractions, petroleum ether fraction demonstrated the highest DPPH scavenging activity with IC50 of 62.45 μg/ml, as long as, chloroform extract exhibited the lowest activity with IC50 of 32.13 μg/ml and N-hexane fraction with IC50 of 58.45 μg/ml. The presences of endogenous substances in Ziziphus jujuba that may act as antioxidant were established by measuring the total content of phenolic and flavonoid activities. In antimicrobial activities, the petroleum ether and methanol extract showed significant activity of 15-18 mm and 11-16 mm zone of inhibition against Bacillus cereus and micrococcus luteus respectively.